The Hmong of Australia Culture and Diaspora - Tapp, Nicholas (ANU Press, 2010)
The Hmong are among Australia's newest immigrant populations. They came as refugees from Laos after the communist revolution of 1975 ended their life there as highland shifting cultivators. The Hmong originate from southern China where many still remain, and others live in Vietnam, Thailand and Burma. Hmong refugees are now also settled in the USA, Canada, France, Germany and French Guyana. Already the beauty and richness of traditional Hmong culture, in particular their shamanism and embroidered costume, has attracted the attention of the Australian public, but little is known about these people, their background or the struggles they have faced to adjust to a new life in Australia.This interdisciplinary collection of articles deals with their music and textiles, gender and language, their social adaptation and their global diaspora. The book aims to bring knowledge of the Hmong to a wider public and contribute to the understanding of these people.